Deuterium and snow hydrology - Judy, Clark Henry, author; Meiman, James R. (James Richard), advisor; Friedman, Irving, committee member; Striffler, William D. (William David), committee member; Tompkin, G., committee member; McKee, Blaine K., committee member (Colorado State University. Libraries, 1970)
HDO samples from natural and laboratory snowpacks show that snowpack metamorphism can reduce the initial variability in the HDO content of snow. Field studies in Colorado indicated melt water percolation reduced the variability from a spread of -229%o to -106% relative to Standard Mean Ocean Water for fresh snow to a spread of -182%a to -158%o for the snowpack in the middle of the melt period. Further studies in the laboratory indicated that isotopic fractionation and vapor transport occurring during depth hoar formation may homogenize the lower part of the snowpack before melt occurs. The homogenization of the HDO content of the snowpack would reduce the problems involved in following snowmelt through the hydrologic system. Preliminary studies indicated three unexpected results. No clear relationship was found between the HDO content of fresh snow and altitude. Fractionation did occur during sublimation from a snow surface. Depth hoar formation appeared to occur because of a continuous diffusion of material, not exclusively by a crystal-to-crystal transfer of mass.
Covers not scanned. Item deaccessioned after digitization.
Keywords: Snow; Deuterium